Copper-catalyzed diastereoselective synthesis of β-boryl-α-quaternary carbon carboxylic esters. Issue 47 (26th November 2018) - Zuo, Ya-Jie; Zhong, Zhuoran; Fan, Yinkun; Li, Xiangyu; Chen, Xiaolu; Chang, Yuwei; Song, Ruihu; Fu, Xinpeng; Zhang, Anling; Zhong, Chong-Min
Abstract : Cu(i )-Catalyzed diastereoselective carboboration of α-alkyl-substituted α, β-unsaturated carboxylic esters to produce β-boryl-α-quaternary carbon esters was developed. Abstract : Cu(i )-Catalyzed diastereoselective carboboration of α-alkyl-substituted α, β-unsaturated carboxylic esters to produce β-boryl-α-quaternary carbon esters was developed. The carbon skeletons of dialkyl sulfates, primary allyl halides, and benzyl bromides were transferred to the α-position of the substrates to provide products in moderate to good yields with a diastereoselectivity of >95% in most cases. Substrates bearing a β-(hetero)aryl substituent gave higher diastereoselectivities than those bearing a linear β-alkyl substituent. The crystal structure of the potassium trifluoroborate derivative shows that the reactions probably go through a copper(i ) enolate intermediate and the diastereoselectivity arises from the electrophilic attack of electrophiles to the less hindered side of the enolates.